Die cast products and their manufacturing method, and sand cast products and their manufacturing method

JP7634309B1Active Publication Date: 2025-02-21KOIWAI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024082024
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-02-07
Filing Date
2024-05-20
Publication Date
2025-02-21
Estimated Expiration
2044-05-20

AI Technical Summary

Benefits of technology

【0032】 本発明によれば、ダイキャスト製品においては、MgとCuの含有量を最適化することにより、FeとMnを含むアルミニウム合金を用いて、溶体化処理することなく中強度高延性の薄物ダイキャスト製品及びその製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634309000001_ABST
    Figure 0007634309000001_ABST
Patent Text Reader

Abstract

The present invention provides a medium-strength, high-ductility die-cast product and a manufacturing method thereof, as well as a medium-strength, high-ductility sand-cast product and a manufacturing method thereof. [Solution] The die-cast product contains 6.0 to 11.0 weight % Si, 0.51 to 1.00 weight % Mg, 0.1 to 1.0 weight % Cu, 0.1 to 0.7 weight % Mn, 0.50 weight % or less Fe, 0.20 weight % or less Ti, 0.03 weight % or less Sr, and a total amount of unavoidable impurities of 0.50 weight % or less, with the balance being Al. The metal structure contains, as Fe compounds, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds, and the metal structure contains, as Cu compounds, Al-Cu-Mg compounds, and precipitates containing Cu atoms and Mg atoms. The die-cast product has a Vickers hardness of 80 Hv or more and 110 Hv or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a die-cast product and its manufacturing method, and a sand-cast product and its manufacturing method. The present invention relates to a method for manufacturing a medium-strength aluminum alloy thin-cast product having a wall thickness of 5 mm or less at least in a part of the product, and a Vickers hardness of 80 Hv or more. A Vickers hardness of 80 Hv is a guideline indicating a tensile strength of 230 MPa or more, a yield strength of 130 MPa or more, and an elongation of 5% or more. [Background technology]

[0002] The main alloy compositions of casting alloys and die-casting alloys are Al-Si-Mg alloys, Al-Si-Cu alloys, and Al-Si-Cu-Mg alloys. In addition, the 4032 alloy, an Al-Si-Cu-Mg alloy, is known as a forging alloy, and Ni is added as an essential element for high-temperature strength. Among these, many casting alloys and die-casting alloys contain Cu as an essential element, but the Cu content exceeds 1.5% by weight. Cu is considered to be an element that improves strength, but it is difficult to achieve sufficient strength by itself unless the Cu content is increased, and the greater the content, the worse the corrosion resistance and castability. In addition, Mg, which is included in the alloy, is added at about 1% by weight as an essential element when used at high temperatures such as in pistons. On the other hand, Mg is treated as an impurity element when used at room temperature, and is not necessarily controlled to be at most 0.5% by weight or less.

[0003] Among die-casting alloys, ADC3 is known as an Al-Si-Mg alloy. A trace amount of Cu is listed as an impurity element in this alloy. In the forging alloy 4032, Cu, Mg, and Ni are added as essential elements with an upper limit of 1.3% by weight. These alloys containing Cu are different from Al-Si-Mg alloys in that Fe is treated as an impurity and the upper limit is high at around 1% (see, for example, Non-Patent Document 1).

[0004] Except for die-cast parts, thick-walled parts have been the mainstream for most automobile parts. However, with the recent shift to electric vehicles, there has been active development of thinner die-cast parts for large vehicle bodies, including battery cases, rear and front parts. In parallel with this, development of large thin sand castings as pre-verification for confirming the performance of die-cast parts has also progressed (for example, see Patent Document 1).

[0005] When considering application to such fields, good mechanical properties, particularly ductility, elongation and bendability, cannot be expected from the cast material when general die casting methods are used. This is because, unless the inside of the mold is evacuated or depressurized, the product will contain numerous air entrapment defects, and blisters will occur on the product surface when heat treated, so that the general elongation of the as-cast product is 2% or less (for example, see Non-Patent Document 2).

[0006] On the other hand, if high ductility is required, a product with medium strength and high ductility of 250 MPa or more can be considered by using an alloy such as Silafont, which has a low content of Fe and Cu and the addition of Mn, using a vacuum die casting method. However, there are some issues with the cost.

[0007] To improve the quality of these castings, it is effective to carry out solution treatment to granulate the eutectic silicon, followed by water cooling and artificial aging. However, heat treatment is possible for products manufactured by vacuum die casting and sand castings that do not have air entrapment, so it is possible to improve the mechanical properties.

[0008] However, as mentioned above, when a thin and large item is produced, solution treatment and subsequent quenching are not easy due to the problem of deformation of the casting, and there are issues with the commonly used heat treatment method, i.e., quenching by water cooling from the solution treatment temperature (for example, an average cooling rate of 50°C / sec or more).

[0009] For this reason, in the case of sand-mold thin-walled castings, unless high strength is required, forced air cooling from the solution treatment temperature to room temperature is performed using a fan or mist (for example, average cooling rate of 0.3°C / sec to 2.0°C / sec). However, this may not achieve the desired strength. In addition, whether after water quenching or air cooling with a fan, distortion correction is required after the temperature drops to room temperature and before artificial aging. Leaving the casting at room temperature can have well-known negative effects, such as the fact that strength does not increase sufficiently even after artificial aging.

[0010] For example, in the case of JIS AC4C alloy, even if the holding time until artificial aging after solution treatment and water quenching is 15 minutes, it has been reported that the strength is reduced compared to when artificial aging is performed immediately after water quenching. For this reason, a simple method to obtain high strength is to raise the artificial aging temperature to a slightly higher level of 180°C, or to age for a long time, for example, more than 6 hours at 160°C. However, when such heat treatment conditions are selected, the proof stress is somewhat higher than that of a die-cast product without heat treatment, and the mechanical properties are not necessarily the same. As described above, there is a difference in quality, and the heat treatment process is complicated, which leads to increased costs (for example, see Non-Patent Document 3).

[0011] Regarding heat treatment for die casting, in order to reduce the complexity of heat treatment for die cast products and to eliminate solution treatment, it has been proposed to add several times more Sr than the amount added for general improving treatment agents to show high elongation, and to add aging treatment to improve tensile strength to show the specified mechanical properties. However, in die cast products, aging treatment should be avoided if possible (for example, see Patent Document 2). [Prior art documents] [Non-patent literature]

[0012] [Non-Patent Document 1] Kitaoka et al.: Light Metals, 1988, vol. 38, p. 426 [Non-Patent Document 2] Japan Light Metal Association, The Real Strength of Aluminum Alloy Castings [Non-Patent Document 3] Adachi et al.: Light Metals, 37 (1987), 524 [Patent documents]

[0013] [Patent Document 1] Special publication 2023-510881 [Patent Document 2] Japanese Patent Application Publication No. 1-283336 Summary of the Invention [Problem to be solved by the invention]

[0014] The present invention has been made against the above background.

[0015] In mass production methods such as die casting, where the production time is about one minute, it is desirable to avoid heat treatment to obtain the required mechanical properties, as well as the associated distortion correction work, as much as possible. In that sense, although this alloy has high properties with solution treatment, quenching, and artificial aging, it is desirable not to perform solution treatment, that is, to use it as-cast, or if heat treatment is performed, to limit it to T5 treatment (aging treatment after casting), and the material for this die cast product is required to have medium strength and high ductility mechanical properties.

[0016] Moreover, when considering cost reduction of die cast products, it is desirable to use alloys that contain a certain amount of Fe to prevent seizure of the die, while still ensuring ductility, rather than alloys with a low Fe content.

[0017] On the other hand, even in sand casting, where the time from casting to mold opening is as long as about 10 minutes to about a day, it is desirable to avoid heat treatment to obtain the desired mechanical properties as in die casting, and to avoid the distortion correction work that occurs as a result. In that sense, it is desirable to avoid at least solution treatment that does not involve water quenching, that is, to use the as-cast product or T5 treatment (post-cast aging treatment).

[0018] However, if solution treatment is required due to the mechanical properties, the casting must be left at room temperature for an hour after forced air cooling or water quenching before distortion can be corrected. Even if the casting is then artificially aged, it is required to have mechanical properties of 230 MPa or more (equivalent to a Vickers hardness of 80 Hv or more), which is the same as AC4CH die castings, a medium-strength, high-ductility alloy generally used in almost all wheels, which are important safety parts for automobiles. In particular, it is required to have tensile properties and hardness close to those of die-cast products. This is because it is desirable for sand mold prototype castings to be useful for design consideration of die-cast products and dies, rather than simply being required to have high strength and high ductility.

[0019] The above is from the viewpoint of improving ductility. However, from the viewpoint of improving strength, there are many issues remaining. If the so-called T6 treatment, which consists of solution treatment, water quenching, and aging treatment, is not used, there are the following issues. When attempting to achieve a medium strength of 80Hv or more in Vickers hardness and 230MPa or more in the as-cast state or by T5 treatment, in either the sand casting or die casting mold, the Mg-Si compound, which is a precipitate that contributes to age hardening in the mold, tends to become overaged and precipitate coarsely in the mold, resulting in softening and making it difficult to achieve strength.

[0020] On the other hand, the T6 treatment has the following problems. When a casting is solution-treated, it is necessary to straighten the distortion before artificial aging after water quenching or forced air cooling in the atmosphere. Therefore, since it is held in the atmosphere, it is difficult to obtain the desired strength unless the appropriate aging conditions are selected after artificial aging at room temperature. As already mentioned above, if the conditions are selected to eliminate the negative effects, the yield strength is somewhat higher than that of a die-cast product without heat treatment, considering its tensile strength, and it is difficult to obtain the same mechanical properties. [Means for solving the problem]

[0021] In order to solve the above problems, a first aspect of the present invention provides a die-cast product comprising 6.0 to 11.0 weight % Si, 0.51 to 1.00 weight % Mg, 0.1 to 1.0 weight % Cu, 0.1 to 0.7 weight % Mn, 0.50 weight % or less Fe, 0.20 weight % or less Ti, 0.03 weight % or less Sr, and a total amount of unavoidable impurities of 0.50 weight % or less, with the balance being Al, containing, as Fe compounds in the metallographic structure, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds, and containing, as Cu compounds in the metallographic structure, Al-Cu-Mg compounds, and precipitates containing Cu atoms and Mg atoms, and having a Vickers hardness of 80 Hv or more and 110 Hv or less.

[0022] Alternatively, the die-cast product according to the first aspect of the present invention contains one or more of 6.0 to 8.9 weight % Si, 0.51 to 0.80 weight % Mg, 0.1 to 0.6 weight % Cu, 0.31 to 0.50 weight % Mn, 0.40 weight % or less Fe, and 0.003 to 0.030 weight % Sr.

[0023] In the manufacturing method of a die-cast product according to the first aspect of the present invention, a molten aluminum alloy is poured into a product portion of a die and solidified within the product portion of the die. The time from pouring to removing the casting from the product portion of the die is set to within one minute, and age hardening is advanced within that time to manufacture the die-cast product.

[0024] After casting using the die casting method, the casting reaches a specified hardness through age hardening before being removed from the mold. However, if the dissolved Cu and Mg atoms still remain in the aluminum matrix, age hardening will progress slightly to a range of 110 Hv or less when left at room temperature after removal.

[0025] A second aspect of the present invention provides a sand casting product comprising 4.0 to 11.0 weight % Si, 0.51 to 0.80 weight % Mg, 0.1 to 1.0 weight % Cu, 0.2 weight % or less Mn, 0.30 weight % or less Fe, 0.20 weight % or less Ti, 0.005 to 0.030 weight % Sr, and a total amount of unavoidable impurities of 0.50 weight % or less, with the balance being Al, containing eutectic Si independently dispersed in the metallographic structure, containing, as Fe compounds in the metallographic structure, one or more of an Al-Fe-Si compound and an Al-Fe-Si-Mn compound, and an Al-Fe-Si-Mg compound, and containing, as Cu compounds in the metallographic structure, an Al-Cu-Mg compound, and precipitates containing Cu atoms and Mg atoms, and having a Vickers hardness of 80 Hv or more and 110 Hv or less.

[0026] Alternatively, the sand casting product according to the second aspect of the present invention contains one or more of 0.51 to 0.70 weight % Mg, 0.1 to 0.6 weight % Cu, 0.15 weight % or less Fe, and 0.005 to 0.020 weight % or less Sr.

[0027] In the manufacturing method of a sand cast product according to the second aspect of the present invention, a molten aluminum alloy is poured into a sand mold, and the casting removed from the sand mold is subjected to a solution treatment, then water quenching or forced air cooling in the atmosphere, and after 15 minutes or more in the atmosphere, an artificial aging treatment at 140°C to 200°C is performed.

[0028] A third aspect of the present invention provides a sand casting product comprising 4.0 to 11.0 weight % Si, 0.51 to 0.80 weight % Mg, 0.1 to 1.0 weight % Cu, 0.2 weight % or less Mn, 0.30 weight % or less Fe, 0.20 weight % or less Ti, 0.005 to 0.030 weight % Sr, and a total amount of unavoidable impurities of 0.50 weight % or less, with the balance being Al, containing, as Fe compounds in the metallographic structure, one or more of an Al-Fe-Si compound and an Al-Fe-Si-Mn compound, and an Al-Fe-Si-Mg compound, and containing, as Cu compounds in the metallographic structure, an Al-Cu-Mg compound and precipitates containing Cu atoms and Mg atoms, and having a Vickers hardness of 80 Hv or more and 110 Hv or less.

[0029] Alternatively, the sand casting product according to the third aspect of the present invention contains one or more of 0.51 to 0.70 weight % Mg, 0.1 to 0.6 weight % Cu, 0.15 weight % or less Fe, and 0.005 to 0.020 weight % or less Sr.

[0030] In a method for producing a sand cast product according to a third aspect of the present invention, a molten aluminum alloy is poured into a sand mold, and the molten aluminum alloy in the sand mold is solidified at an average cooling rate of 0.8°C / second or more in a solidification region from the melting point to the binary eutectic temperature of 577°C. Thereafter, the casting in the sand mold is cooled at an average cooling rate of 0.08°C / second or more in a temperature region from 300°C to 200°C. The casting is then removed from the sand mold and subjected to an artificial aging treatment.

[0031] Alternatively, in the method for producing a sand cast product according to the third aspect of the present invention, the artificial aging treatment is carried out at a temperature in the range of 140°C to 200°C. Effect of the Invention

[0032] According to the present invention, by optimizing the contents of Mg and Cu in die-cast products, a thin die-cast product with medium strength and high ductility is provided using an aluminum alloy containing Fe and Mn without solution treatment, and a manufacturing method thereof.

[0033] According to the present invention, in a sand casting product, by optimizing the contents of Mg and Cu, an aluminum alloy with a reduced amount of Fe and added Sr is used, and after solution treatment, water quenching or forced air cooling is performed, and after 15 minutes or more in the air, artificial aging treatment is performed, thereby providing a thin sand casting product with medium strength and high ductility and a manufacturing method thereof.

[0034] According to the present invention, a thin sand-cast product with medium strength and high ductility and a method for manufacturing the same are provided by optimizing the contents of Mg and Cu, using an Al alloy with a reduced amount of Fe and added Sr, and further controlling the cooling conditions during and after solidification of the casting in the sand mold cast into the mold and performing aging treatment. [Brief description of the drawings]

[0035] [Figure 1] FIG. 4 is a photograph showing the metal structure of Comparative Example 2. [Diagram 2] FIG. 4 is a photograph showing the metal structure of Example 2. [Diagram 3] FIG. 1 is a photograph showing the metal structure of Example 6. [Figure 4] FIG. 1 is a low-magnification photograph showing the metal structure of Example 6. [Diagram 5] FIG. 2 is a photograph showing the metal structure of a die-cast product. [Figure 6] Photographs showing the metal structure of a sand casting product before and after solution treatment. [Figure 7] FIG. 2 is a photograph showing the effect of solution treatment temperature on the metal structure of a sand casting product. [Figure 8] 1 is a graph showing the effect of solution treatment temperature on the tensile strength of a sand cast product. [Figure 9] 1 is a graph showing the effect of solution treatment temperature on the yield strength of a sand cast product. [Figure 10] 1 is a graph showing the effect of solution treatment temperature on the elongation of a sand cast product. [Figure 11] 1 is a graph showing the effect of solution treatment temperature on the hardness of a sand casting product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] Various embodiments of the present invention will now be described in detail.

[0037] [First embodiment] The die-cast product according to the first embodiment of the present invention contains 6.0 to 11.0 weight % Si, 0.51 to 1.00 weight % Mg, 0.1 to 1.0 weight % Cu, 0.1 to 0.7 weight % Mn, 0.50 weight % or less Fe, 0.20 weight % or less Ti, 0.03 weight % or less Sr, and a total amount of unavoidable impurities of 0.50 weight % or less, with the balance being Al. The die-cast product contains, as Fe compounds in the metal structure, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds, and contains, as Cu compounds in the metal structure, Al-Cu-Mg compounds, and precipitates containing Cu atoms and Mg atoms, and has a Vickers hardness of 80 Hv or more and 110 Hv or less.

[0038] In this specification, the term "unavoidable impurities" refers to elements other than Al, Si, Mg, Cu, Mn, Fe, Ti, and Sr, such as V, Cr, P, Pb, Sn, etc. The oxygen element is not included in the "unavoidable impurities".

[0039] (Die-cast products) In the die-cast product of this embodiment, if the Si content is too low, the molten metal flow during production is poor, and if the Si content is too high, the ductility is reduced. In this embodiment, the Si content is 6.0 to 11.0 wt. %. To further increase the ductility, the Si content is preferably 6.0 to 8.9 wt. %.

[0040] In the die-cast product of this embodiment, Mg forms nm-sized precipitates with Cu and Al, contributing to improving strength. However, if too much Mg is added, ductility decreases. In this embodiment, the Mg content is 0.51 to 1.00 wt%. To further increase ductility, the Mg content is preferably 0.51 to 0.80 wt%.

[0041] In the die-cast product of this embodiment, Cu forms nm-sized precipitates together with Al and Mg, contributing to improving strength. However, if the Cu content is too high, corrosion resistance and ductility decrease. In this embodiment, the Cu content is 0.1 to 1.0 wt %. Preferably, the Cu content is 0.1 to 0.6 wt %.

[0042] The precipitates that contribute to the strength improvement contain Cu and Mg atoms. The precipitates include at least one of the following: a GP zone consisting of Cu and Mg atoms that are completely coherent with the Al matrix, and a semi-coherent intermediate phase consisting of Al-Cu-Mg precipitates. Although there are μm-sized Al-Cu-Mg compounds in the metal structure that can be confirmed with an optical microscope, the μm-sized Al-Cu-Mg compounds do not play a large role in the strength.

[0043] In the die-cast product of this embodiment, Mn improves ductility by changing the shape of the contained Fe compound from needle-like to block-like. However, if the amount of Mn added is too large, the ductility decreases, so the amount of Mn is set to 0.1 to 0.7% by weight. Preferably, the amount of Mn is set to 0.31 to 0.50% by weight.

[0044] In the die-cast product of this embodiment, Fe is added to prevent seizure, but if the amount added is too large, it can cause a decrease in ductility, so the Fe amount is set to 0.50% by weight or less, and preferably, the Fe amount is set to 0.40% by weight or less.

[0045] In the die-cast product of this embodiment, Ti is added as a grain refiner for the purpose of suppressing the occurrence of shrinkage cavities in the cast product. Since there is no improvement in effect even if Ti is added in an amount exceeding 0.20 wt%, the Ti content is set to 0.20 wt% or less.

[0046] In the die-cast product of this embodiment, the amount of Sr required for refining eutectic Si varies depending on the amount of P impurity contained in the molten alloy, but considering the certainty of the refining effect, the amount of Sr is set to 0.03 wt% or less. However, if the amount of Sr is too much, Sr oxide is formed and mixed into the product, degrading the quality, so the amount of Sr is preferably 0.003 to 0.030 wt%.

[0047] (Metal structure of die-cast products) The die-cast product in this embodiment contains, in its metal structure, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds as Fe compounds, and Al-Cu-Mg compounds and precipitates containing Cu and Mg atoms as Cu compounds. Note that the Al-Cu-Mg compounds include Al-Cu-Mg-Si compounds that contain Si in addition to Cu and Mg.

[0048] The sizes of Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, Al-Fe-Si-Mg compounds, Al-Cu-Mg compounds, and the like in the metal structure are mainly 2 μm or more, and can be measured by observing the structure using an optical microscope, for example.

[0049] The size of the precipitates containing Cu atoms and Mg atoms in the metal structure is, for example, about 3 nm to 60 nm. The precipitates include, for example, GP zones and intermediate phases as metastable phases.

[0050] The GP zone refers to the arrangement of atoms in the precipitates when heat treated. In the GP zone, the aluminum atoms of the parent phase and the Cu and Mg atoms dissolved in the parent phase are in a state of alignment in the crystal lattice. For example, in the GP zone, the dissolved Cu and Mg atoms are bonded to the surrounding Al atoms. When a precipitate contains a GP zone, it contributes to age hardening.

[0051] The intermediate phase is a state in which the aluminum of the parent phase and the Cu atoms, Mg atoms, etc., dissolved in the parent phase are partially matched, and can also be said to be in a semi-matched state. When the precipitates include an intermediate layer, they also contribute to age hardening.

[0052] The sizes of the GP zone and the intermediate phase in the metal structure can be measured, for example, by observing the structure using a transmission electron microscope.

[0053] When the precipitates precipitate as a stable phase, they simply disperse in the aluminum matrix as coarse precipitates, and these coarse precipitates do not contribute to age hardening.

[0054] (Manufacturing method of die-cast products) The die casting method is a method in which molten metal is injected into a die cavity and then the casting is removed from the die cavity within a matter of minutes. The manufacturing method is as follows:

[0055] The molten metal is poured into a tube called a sleeve, and then a tip that fits into the sleeve is moved at an injection speed of about several meters per second to fill the mold with the molten metal, which is then pressurized with a metal pressure of, for example, 50 MPa or more to solidify. The solidification time is no longer than 5 seconds. The mold is then opened and the die-cast product is removed from the mold. The mold is opened after the molten aluminum in the biscuit part has solidified. The biscuit part is the part that connects to the mold product part, and solidifies more slowly than the mold product part. Therefore, as the volume of the biscuit increases, the solidification time increases, but from the viewpoint of productivity, the removal time is within 1 minute. Furthermore, age hardening progresses during the time until removal.

[0056] A method for manufacturing a die-cast product in this embodiment is, for example, as follows.

[0057] Molten aluminum alloy is poured into a mold, and then the molten aluminum alloy is quenched in the mold. At the solidification temperature at which the alloy changes from liquid to solid, μm-sized Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, Al-Fe-Si-Mg compounds, and Al-Cu-Mg compounds are crystallized. In addition, during the quenching process in the mold, Cu atoms and Mg atoms are dissolved in the atomic state in the primary aluminum that is generated first as a supersaturated solid solution.

[0058] During the cooling process in the mold, around 200°C, the precipitation of nm-sized precipitates is promoted. In particular, in the case of continuous precipitation, age precipitation or phase decomposition is promoted by nucleation and its growth, or spinodal decomposition. The precipitates contain, for example, Cu atoms and Mg atoms, and contribute to age hardening.

[0059] [Example] (Comparative Examples and Examples of Die-cast Products) Table 1 shows the chemical composition and mechanical properties of the vacuum-cast die-cast product. The die-cast product has a rectangular cross section, and is 50 mm wide and 150 mm long, consisting of 1.5 mm, 3.5 mm, and 9.0 mm sections. The casting weight is 230 g. After the molten metal was injected and filled into the mold, the gate on the tip side solidified and the pressure was no longer effective in the 1.5 mm and 9.0 mm sections, which had shrinkage cavities. Therefore, the 3.5 mm section, which was a healthy part with almost no shrinkage cavities, was used for the test. The casting test was carried out as follows. The molten metal was injected into the sleeve using a die-casting machine, and a metal pressure of 50 MPa was applied, and the solidified cast product was then opened and removed within 10 seconds.

[0060] [Table 1]

[0061] Comparative Example 1 is an Al-Si-Mg alloy, and does not contain Cu, unlike the present embodiment. Therefore, when solidified in the mold, it is prone to overaging, and the Vickers hardness of Comparative Example 1 is low at 75 Hv.

[0062] Comparative Examples 2 and 3 contain 0.30 wt% Mg, which is lower than the range of the chemical composition of this embodiment. Comparative Examples 2 and 3 contain a certain amount of Cu, so they have a Vickers hardness of 80 Hv or more and a tensile strength of 250 MPa or more. However, when comparing the effects of heat treatment through a test assuming the thermal effects when the product is held in the mold for a long time (Comparative Example 2 is 400°C x 0 minutes, Comparative Example 3 is 400°C x 2 minutes), the heat-treated Comparative Example 3 is softer than the non-heat-treated Comparative Example 2, and the chemical compositions of Comparative Examples 2 and 3 leave the quality unstable due to the thermal effects of the product wall thickness in the mold and the time in the mold.

[0063] Comparative Examples 4 and 5 contain 0.26 wt% Cu and 0.45 wt% Mg, which is lower than the present embodiment. Comparative Examples 4 and 5 also have a Vickers hardness of 85 Hv. However, in tests assuming similar heat effects (Comparative Example 4 at 400°C for 0 minutes, Comparative Example 5 at 400°C for 2 minutes), the heat-treated Comparative Example 5 is softer than the unheated Comparative Example 4, and the chemical compositions of Comparative Examples 4 and 5 show instability in quality due to heat effects in the mold.

[0064] Comparative Example 6 contains 1.1 wt % Mg, which is more than the present embodiment. Comparative Example 7 contains 1.2 wt % Cu, which is more than the present embodiment. In Comparative Examples 6 and 7, the Vickers hardness exceeds 100 Hv, but the elongation is low at 3%.

[0065] Comparative Example 8 contains 0.68% by weight of Fe, which is more than the present embodiment. In Comparative Example 8, the amount of Fe is so high that the elongation is low at 3%.

[0066] On the other hand, all of Examples 1 to 15, which are within the chemical composition range of this embodiment, exhibit a Vickers hardness of 80 Hv or more, a yield strength of 140 MPa or more, and an elongation of 5% or more.

[0067] In addition, in Examples 1 to 15, the difference is small even before and after the same test (400°C) as the Comparative Example, which assumes the thermal effects in the mold. For example, Examples 2, 3, 4, 5, 6, 7, 8, 9, 10, and 11 show the difference between heat treatment (400°C x 0 minutes) and no heat treatment (400°C x 2 minutes) for the same chemical composition. In all cases, the hardness and tensile strength do not change significantly with or without heat treatment, and the quality is stable with little effect from heat.

[0068] In addition, in Examples 1 to 15, it is also possible to improve the elongation by reducing the amounts of Mg, Cu, Si, and Fe.

[0069] Fig. 1 shows the metal structure of Comparative Example 2. The metal structure of Comparative Example 2 contains Al-Fe-Si compounds that are large needle-like crystals with a length of about 10 µm, and also contains Al-Cu-Mg compounds between the Al-Fe-Si compounds.

[0070] Fig. 2 shows the metal structure of Example 2. The metal structure of Example 2 contains Al-Fe-Si compounds and Al-Fe-Si-Mg compounds that are needle-like crystals with lengths of about 10 µm or less, and contains Al-Cu-Mg compounds therebetween.

[0071] Fig. 3 shows the metal structure of Example 6. Fig. 4 shows the metal structure of Example 6 at a low magnification. The metal structure of Example 6 contains, as Fe compounds, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds. The metal structure also contains, as Cu compounds, Al-Cu-Mg compounds and precipitates containing Cu atoms and Mg atoms.

[0072] Fig. 5 is a photograph showing the metal structure of the die-cast product. The die-cast product shown in Fig. 5 contains 8.7 wt% Si, 0.6 wt% Mg, 0.3 wt% Cu, 0.3 wt% Fe, 0.4 wt% Mn, and the balance is Al.

[0073] Generally, the metal structure of die casting consists of primary crystal α-Al, a mixed structure of eutectic Si and eutectic Al, and other compounds. When molten aluminum alloy in a cylinder called a sleeve is injected and filled into a mold, if the temperature of the molten alloy in the sleeve just before injection is within 50℃ of the melting point of the molten alloy, the lower the temperature, especially within 30℃, the more fine granular Al with a diameter of 10μm or less will be generated in addition to the petal-like or spherical primary crystal α-Al.

[0074] Primary α-Al is the solid that first emerges from the liquid as the molten metal solidifies after being filled into the mold. For example, as shown in Figure 5, the morphology of primary α-Al can be dendritic, petal-like, or spherical. The fine granular Al is presumably generated from the liquid with a high Si content (approximately 12% by weight in terms of Si weight%) that exists after the generation of primary α-Al during the solidification process, and is considered to be Al that emerged before eutectic Si. Then, eutectic Al and eutectic Si emerge simultaneously, and solidification is completed.

[0075] In addition, in Figures 1 to 3, the compounds were determined and described based on the results of crystal orientation analysis using a backscattered electron diffraction (EBSD) device attached to the SEM and element mapping using an energy dispersive X-ray spectroscopy (EDS) device in the backscattered electron (BSE) images taken with a scanning electron microscope (SEM). Figures 4 and 5 show the results of observation using an optical microscope.

[0076] [Second embodiment] The sand casting product according to the second embodiment of the present invention contains 4.0 to 11.0 weight % Si, 0.51 to 0.80 weight % Mg, 0.1 to 1.0 weight % Cu, 0.2 weight % or less Mn, 0.30 weight % or less Fe, 0.20 weight % or less Ti, 0.005 to 0.030 weight % Sr, and unavoidable impurities in a total amount of 0.50 weight % or less, with the balance being Al. It contains eutectic Si independently dispersed in the metallographic structure, contains as Fe compounds in the metallographic structure any one or more of an Al-Fe-Si compound and an Al-Fe-Si-Mn compound, and an Al-Fe-Si-Mg compound, contains as Cu compounds in the metallographic structure an Al-Cu-Mg compound, and precipitates containing Cu atoms and Mg atoms, and has a Vickers hardness of 80 Hv or more and 110 Hv or less.

[0077] In the manufacturing method of a sand cast product according to the second embodiment of the present invention, a molten aluminum alloy is poured into a sand mold, and the casting removed from the sand mold is subjected to a solution treatment, then water quenching or forced air cooling in the atmosphere, and after 15 minutes or more in the atmosphere, an artificial aging treatment at 140°C to 200°C is performed.

[0078] Among gravity casting methods, the cooling rate of sand casting is 1 / 10 to 1 / 100 of the cooling rate at solidification obtained by die casting. Therefore, the metal structure of castings obtained by sand casting is not as fine as that obtained by die casting, and it is not easy to obtain high ductility.

[0079] Unlike die casting, sand casting, which does not involve seizure between the mold and molten metal, is best done to minimize the amount of Fe in order to reduce the amount of iron compounds that cause reduced ductility. Reducing the amount of Si is also effective. If necessary, a small amount of Mn can be added to change the shape of the needle-like iron compounds to granular. When performing solution treatment, it is effective to granulate the eutectic Si, which is the starting point of cracks.

[0080] (Sand casting products) In the sand casting product of this embodiment, if the Si content is too low, the fluidity during production is poor, and if the Si content is too high, the ductility is reduced. In this embodiment, the Si content is set to 4.0 to 11.0 wt %.

[0081] In the sand casting product of this embodiment, Mg forms nm-sized precipitates with Cu and Al, which contributes to improving strength. However, if too much Mg is added, ductility decreases. In this embodiment, the Mg content is 0.51 to 0.80 wt%. Preferably, the Mg content is 0.51 to 0.70 wt%.

[0082] In the sand casting product of this embodiment, Cu forms nm-sized precipitates together with Al and Mg, contributing to improving strength. However, if the Cu content is too high, corrosion resistance and ductility decrease. In this embodiment, the Cu content is 0.1 to 1.0 wt %. Preferably, the Cu content is 0.1 to 0.6 wt %.

[0083] In the sand casting product of this embodiment, Mn is added from the viewpoint of improving ductility by forming a compound with Fe. However, since the amount of Fe itself is small in this embodiment, the amount of Mn is set to 0.2 wt% or less.

[0084] In the sand cast product of this embodiment, from the viewpoint of improving ductility, the Fe content is set to 0.30% by weight or less, and preferably, the Fe content is set to 0.15% by weight or less.

[0085] In the sand casting product of this embodiment, Ti is added as a grain refiner for the purpose of suppressing the occurrence of shrinkage cavities in the casting product. Since there is no improvement in effect even if Ti is added in an amount exceeding 0.20 wt%, the Ti content is set to 0.20 wt% or less.

[0086] In the sand casting product of this embodiment, the amount of Sr required for refining eutectic Si varies depending on the amount of P impurity contained in the molten alloy, but considering the certainty of the refining effect, the amount of Sr is set to 0.005 to 0.030% by weight. However, if the amount of Sr is too much, Sr oxides are formed and mixed into the product, lowering the quality. Preferably, the amount of Sr is set to 0.005 to 0.020% by weight.

[0087] (Metal structure of sand casting products) The sand casting product in this embodiment contains eutectic Si dispersed independently in the metal structure. The Fe compounds contained in the metal structure include at least one of an Al-Fe-Si compound and an Al-Fe-Si-Mn compound, and an Al-Fe-Si-Mg compound. The Cu compounds contained in the metal structure include an Al-Cu-Mg compound and precipitates containing Cu and Mg atoms. The Al-Cu-Mg compound may also include an Al-Cu-Mg-Si compound containing Si in addition to Cu and Mg.

[0088] The eutectic silicon that is dispersed independently in the metal structure is formed, for example, by solution treatment at about 500°C, when the eutectic silicon that was connected in a mesh-like shape breaks apart, becomes granular, and becomes independent.

[0089] Furthermore, by performing solution treatment at a temperature exceeding 500° C., a certain proportion of the Cu atoms and Mg atoms that constitute the Al-Cu-Mg compound are temporarily dissolved in the aluminum matrix.

[0090] Figure 6 is a photograph showing the metal structure of a sand casting product before and after solution treatment. Figure 6 shows the results of observation using an optical microscope. As shown in Figure 6, the metal structure changes before and after solution treatment. The metal structure contains an aluminum parent phase, Al-Cu-Mg compounds, and compounds containing iron. In the structure shown in Figure 6, the brightest part is the aluminum parent phase.

[0091] In the structure shown in Figure 6, the darkest part, indicated by the black arrow, is an Al-Cu-Mg compound. For example, as shown in Figure 6(a), the Al-Cu-Mg compound has a shape surrounded by linear outlines, e.g., a polygonal shape, before solution treatment. On the other hand, as shown in Figure 6(b), the Al-Cu-Mg compound has a shape with a smooth outline after solution treatment at, e.g., 530°C for 2 hours.

[0092] In the structure shown in Figure 6, the areas with intermediate brightness between the Al-Cu-Mg compounds and the aluminum parent phase, and indicated by white arrows, are compounds containing Fe. For example, as shown in Figures 6(a) and 6(b), the morphology of compounds containing Fe changes little before and after solution treatment.

[0093] The sizes of the Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, Al-Fe-Si-Mg compounds, and Al-Cu-Mg compounds in the metal structure are mainly 2 μm or more.

[0094] The size of the precipitates containing Cu atoms and Mg atoms in the metal structure is, for example, about 3 nm to 60 nm. The precipitates include, for example, GP zones and intermediate phases as metastable phases, similar to those in the first embodiment.

[0095] (Method of manufacturing sand casting products) A method for producing a sand cast product in this embodiment is, for example, as follows.

[0096] Molten aluminum alloy is poured into a sand mold and then solidified in the sand mold. In the solidification temperature range where the alloy changes from liquid to solid, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, Al-Fe-Si-Mg compounds, and Al-Cu-Mg compounds are crystallized. During the cooling process after solidification in the sand mold, coarse precipitates containing Cu and Mg atoms may be generated.

[0097] The casting removed from the sand mold is subjected to a solution treatment. Fig. 7 is a photograph showing the effect of the solution treatment temperature on the metal structure of a sand-cast product. Fig. 7 shows the results of observation using an optical microscope. Figs. 8 to 11 are graphs showing the effects of the solution treatment temperature and treatment time on the tensile strength, proof stress, elongation, and Vickers hardness of a sand-cast product.

[0098] For example, as shown in Figure 7(b), in solution treatment up to 530°C, the burning caused by the melting of compounds containing Cu in the metal structure is small and not very noticeable. However, as shown in Figure 7(c), when solution treatment is performed at 550°C, the burning phenomenon becomes noticeable. As a result, a large amount of Cu and Mg is dissolved in the aluminum matrix, which tends to increase the yield strength (Figure 9) and Vickers hardness (Figure 11). On the other hand, tiny cavities (pores larger than 30 μm) occur after the Al-Cu-Mg compounds are dissolved, which reduces the elongation (Figure 10).

[0099] As shown in Figure 7(a), burning is unlikely to occur with solution treatment at 500°C or less. However, since Al-Cu-Mg compounds are unlikely to dissolve in the aluminum matrix, long heat treatment times, for example, over 15 hours, are required. Heat treatment times of up to 6 hours are unlikely to improve the strength properties (Figures 8, 9, and 11) and elongation (Figure 10).

[0100] For example, as shown in Figure 10, in order to ensure an elongation of 5% or more, heat treatment is performed at a temperature range of more than 500°C and not more than 540°C. Note that within this temperature range, the required heat treatment time differs depending on the treatment temperature. For example, the heat treatment time for solution treatment is 6 to 12 hours at 510°C, 3 to 10 hours at 520°C, 1 to 8 hours at 530°C, and 0.5 to 2 hours at 540°C.

[0101] Furthermore, as shown in Figure 10, for example, when a higher elongation of 7% or more is to be secured by solution treatment, it is effective to perform heat treatment at 520°C or higher and 540°C or lower. In this temperature range, even if there are minute cavities, their size is 10μm or less. Such minute cavities do not adversely affect the mechanical properties, but rather bring about good mechanical properties.

[0102] After cooling in the sand mold, a solution treatment is performed. The solution treatment is performed, for example, at 520 to 540°C. As a result, Cu atoms and Mg atoms in the coarse precipitates are dissolved in the aluminum in an atomic state. Furthermore, by the solution treatment at a temperature exceeding 500°C, the eutectic Si that was connected in a fibrous form changes to a granular form, both three-dimensionally and two-dimensionally, and is dispersed independently.

[0103] After the solution treatment, the steel is water quenched or forced air-cooled in the air, and after 15 minutes or more in the air, artificial aging treatment is performed. The artificial aging treatment is performed, for example, at 140°C to 200°C. This artificial aging treatment causes nanometer-sized precipitates to precipitate. The precipitates contain, for example, Cu atoms and Mg atoms, and contribute to age hardening.

[0104] [Example] (Comparative Examples and Examples of Sand Cast Products) The chemical composition and mechanical properties of the sand cast product are shown in Table 2. The shape of the sand cast product is a flat plate with a wall thickness of 3 mm, width of 100 mm, length of 100 mm, and casting weight of 400 g. The 3 mm part was used for the test.

[0105] [Table 2]

[0106] The sand cast products were solution treated at 530°C, then removed from the solution furnace and water-cooled or forced air-cooled using a fan (approximately 0.5°C / sec). After that, they were left at room temperature for 2 hours and then subjected to various aging treatments.

[0107] The comparative examples 9 to 14 do not contain Cu, which is different from the range of chemical components of this embodiment. The comparative examples 9 to 12 all show a Vickers hardness of 80 Hv or more, but the tensile strength is 250 to 290 MPa, which does not reach 300 MPa. On the other hand, the tensile strength of the comparative examples 9 to 12 shows a value about 50 MPa higher than the proof strength (170 to 250 MPa) of the comparative examples 9 to 12 obtained by aging treatment after solution treatment and water quenching. However, as shown in the comparative examples 13 and 14, which have the same chemical components as the comparative examples 9 to 12, when the proof strength is reduced by lowering the aging temperature from 180°C to 160°C, both the hardness and the tensile strength are reduced, which is different from the Vickers hardness of 85 Hv or more, the proof strength equivalent to 150 MPa, and the tensile strength equivalent to 300 MPa obtained in the die-cast product (Table 1).

[0108] Examples 16 to 26 are within the range of the chemical composition of this embodiment. In Examples 16 to 26, by selecting the Mg content, Cu content, and Si content, it is possible to exhibit a yield strength of 136 MPa or more and a Vickers hardness of 85 Hv or more, and to ensure a tensile strength equivalent to 300 MPa and good elongation. In Examples 25 and 26, after solution treatment, whether air-cooled or water-cooled, and then left at room temperature, the alloys exhibit higher tensile strength than Comparative Examples 13 and 14 after artificial aging at 160°C.

[0109] [Third embodiment] A sand casting product according to a third embodiment of the present invention contains 4.0 to 11.0 weight % Si, 0.51 to 0.80 weight % Mg, 0.1 to 1.0 weight % Cu, 0.2 weight % or less Mn, 0.30 weight % or less Fe, 0.20 weight % or less Ti, 0.005 to 0.030 weight % Sr, and a total amount of unavoidable impurities of 0.50 weight % or less, with the balance being Al, and contains, as Fe compounds in the metallographic structure, one or more of an Al-Fe-Si compound and an Al-Fe-Si-Mn compound, and an Al-Fe-Si-Mg compound, and contains, as Cu compounds in the metallographic structure, an Al-Cu-Mg compound, and precipitates containing Cu atoms and Mg atoms, and has a Vickers hardness of 80 Hv or more and 110 Hv or less.

[0110] In a manufacturing method of a sand cast product according to a third embodiment of the present invention, a molten aluminum alloy is poured into a sand mold, and the molten aluminum alloy in the sand mold is solidified at an average cooling rate of 0.8°C / second or more in a solidification range from the melting point to the binary eutectic temperature of 577°C. Thereafter, the casting in the sand mold is cooled at an average cooling rate of 0.08°C / second or more in a temperature range from 300°C to 200°C. The casting is then removed from the sand mold and subjected to an artificial aging treatment.

[0111] (Sand casting products with mold cooling control) In the sand casting product of this embodiment, if the Si content is too low, the molten metal flow is poor, and if the Si content is too high, the ductility is reduced. In this embodiment, the Si content is set to 4.0 to 11.0 wt %.

[0112] In the sand casting product of this embodiment, Mg forms nm-sized precipitates with Cu and Al, which contributes to improving strength. However, if too much Mg is added, ductility decreases. In this embodiment, the Mg content is 0.51 to 0.80 wt. %. Preferably, the Mg content is 0.51 to 0.70 wt. %.

[0113] In the sand casting product of this embodiment, Cu forms nm-sized precipitates with Al and Mg, which contributes to improving strength. However, if the Cu content is too high, corrosion resistance and ductility decrease. In this embodiment, the Cu content is 0.1 to 1.0 wt %. Preferably, the Cu content is 0.1 to 0.6 wt %.

[0114] In the sand casting product of this embodiment, Mn is added from the viewpoint of improving ductility by forming a compound with Fe. However, since the amount of Fe itself is small in this embodiment, the amount of Mn is set to 0.2 wt% or less.

[0115] In the sand cast product of this embodiment, from the viewpoint of improving ductility, the Fe content is set to 0.30% by weight or less, and preferably, the Fe content is set to 0.15% by weight or less.

[0116] In the sand casting product of this embodiment, Ti is added as a grain refiner for the purpose of suppressing the occurrence of shrinkage cavities in the casting product. Since there is no improvement in effect even if Ti is added in an amount exceeding 0.20 wt%, the Ti content is set to 0.20 wt% or less.

[0117] In the sand casting product of this embodiment, the Sr content is set to 0.005 to 0.030% by weight in consideration of the reliability of the refinement effect. However, if the Sr content is too high, Sr oxides are formed and mixed into the product, lowering the quality, so the Sr content is preferably set to 0.005 to 0.020% by weight.

[0118] (Metal structure of sand casting products with mold cooling control) The sand casting product in this embodiment contains, in the metal structure, Fe compounds, at least one of Al-Fe-Si compounds and Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds. The metal structure contains, in the metal structure, Cu compounds, Al-Cu-Mg compounds, and precipitates containing Cu and Mg atoms. The precipitates include, for example, the GP zone and intermediate phase described in the first embodiment.

[0119] The sizes of the Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, Al-Fe-Si-Mg compounds, and Al-Cu-Mg compounds in the metal structure are mainly 2 μm or more.

[0120] The size of the precipitates containing Cu atoms and Mg atoms in the metal structure is, for example, about 3 nm to 60 nm. The precipitates include, for example, GP zones and intermediate phases as metastable phases, similar to those in the first embodiment.

[0121] (Manufacturing method of sand casting products by controlling cooling inside the mold) A method for producing a sand cast product in this embodiment is, for example, as follows.

[0122] The molten aluminum alloy is poured into a sand mold, and then cooled in the sand mold. Cooling control in the mold is performed as follows.

[0123] When cooling in the mold, the casting is solidified at an average cooling rate of 0.8°C / sec or more in the solidification section from the melting point to the binary eutectic temperature of 577°C. By increasing the average cooling rate in the solidification section, it is possible to dissolve a large amount of Cu and Mg in the atomic state in the primary aluminum. In addition, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, Al-Fe-Si-Mg compounds, etc. are crystallized in this solidification section and the section up to the final solidification temperature. If the average cooling rate is slower than this, shrinkage cavities are likely to occur inside the casting. Preferably, the average cooling rate is 1.0°C / sec or more.

[0124] After passing through the above solidification zone, the material is cooled at a relatively high average cooling rate of 0.08°C / sec or more in the temperature zone from 300°C to 200°C. This makes it possible to suppress the generation of coarse Al-Cu-Mg precipitates after passing through the above solidification zone, and to prevent a decrease in strength.

[0125] In order to increase the average cooling rate in the solidification section and in the temperature section from 300°C to 200°C, it is possible to use sand with high thermal conductivity, sand with fine grain size, suction from outside the sand mold, cooling from outside the sand mold, and passing water through the sand mold.

[0126] After casting, artificial aging is performed. The artificial aging is performed, for example, in a temperature range of 140°C to 200°C. This artificial aging causes nanometer-sized precipitates to precipitate. The precipitates contain, for example, Cu atoms and Mg atoms, and contribute to age hardening.

[0127] [Example] (Comparative examples and examples of sand casting products with in-mold cooling control) Table 3 shows the chemical composition and mechanical properties of the sand cast product with in-mold cooling control. The shape of the sand cast product is a flat plate with a wall thickness of 3 mm, width of 100 mm, length of 100 mm, and casting weight of 400 g. The 3 mm part was used for the test.

[0128] [Table 3]

[0129] The sand cast products shown in Table 3 were not subjected to solution treatment, but were only subjected to artificial aging treatment after casting.

[0130] In Examples 27 to 41, three types of aging treatments (180°C x 6 hours, 160°C x 9 hours, and 190°C x 2 hours) were performed. When the solidification rate and the cooling rate after solidification of the casting were to be increased, zircon-based sand was used as the sand material.

[0131] In Comparative Examples 15 to 17, silica sand was used. The speed of passage from 300°C to 200°C was slow at 0.06°C / sec or less. Comparative Examples 15 to 17 contained Cu and Mg, but Al-Cu-Mg compounds were coarsely precipitated due to the heat effect during the passage from 300°C to 200°C, and the Vickers hardness was low at 75Hv or less.

[0132] In Comparative Example 18, zircon-based sand was used. The passage speed from 300°C to 200°C was fast at 0.08°C / sec, but the solidification speed was slow at 0.5°C / sec due to the application of a mold wash. Therefore, the amount of solid solution of Cu and Mg was reduced during the temperature drop process, the amount of precipitation hardening during artificial aging treatment (180°C x 6 hours) was small, and the Vickers hardness was low at 70Hv.

[0133] The Cu amount in Comparative Example 19 and the Mg amount in Comparative Example 20 are less than the range of the chemical composition of this embodiment. In Comparative Examples 19 and 20, even if the solidification rate and the cooling rate after solidification of the casting were increased to 1.0° C. / sec and 0.12° C. / sec, respectively, by using zircon-based sand, the Vickers hardness was low at 74 Hv or less.

[0134] Examples 27 to 41 are within the range of the chemical composition of this embodiment. In Examples 27 to 41, the Mg content, Cu content, and Si content were selected, and the solidification rate and the cooling rate after solidification were appropriately controlled within the temperature range of this embodiment, so that all of them exhibited a Vickers hardness of 80 Hv or more.

[0135] [Fourth embodiment] A die-cast product according to a fourth embodiment of the present invention contains 6.0 to 11.0 weight % Si, 0.51 to 1.00 weight % Mg, 0.1 to 1.0 weight % Cu, 0.1 to 0.7 weight % Mn, 0.50 weight % or less Fe, 0.20 weight % or less Ti, 0.03 weight % or less Sr, 0.0050 weight % or less Be, and a total amount of unavoidable impurities of 0.50 weight % or less, with the balance being Al, contains Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds as Fe compounds in the metal structure, contains Al-Cu-Mg compounds and precipitates containing Cu atoms and Mg atoms as Cu compounds in the metal structure, and has a Vickers hardness of 80 Hv or more and 110 Hv or less.

[0136] (Die-cast products) The die-cast product in this embodiment contains Si, Mg, Cu, Mn, Fe, Ti, Sr, and inevitable impurities in the same weight percentages as in the first embodiment, and may further contain Be.

[0137] In the die-cast product of this embodiment, Sr, which is added to improve elongation, has a high oxide generating ability and therefore reduces the fluidity of the molten metal. Furthermore, a high content of Mg reduces the fluidity of the molten metal. Therefore, in order to suppress the oxidation of Sr and Mg and to improve the fluidity of the molten metal, 0.0050% by weight or less of Be is contained. To improve the fluidity of the molten metal, the amount of Be is preferably 0.0005% by weight to 0.0050% by weight.

[0138] (Metal structure of die-cast products) Basically, the die-cast product of this embodiment has the same metal structure as that of the first example.

[0139] (Manufacturing method of die-cast products) Basically, the die-cast product of this embodiment is manufactured in the same manner as in the first embodiment.

[0140] [Example] (Example of a die-cast product) Table 4 shows the chemical composition and mechanical properties of the die-cast product according to this embodiment. The test pieces of the examples shown in Table 4 contain Al, 9.0% by weight of Si, 0.55% by weight of Mg, 0.25% by weight of Cu, 0.4% by weight of Fe, 0.4% by weight of Mn, and 0.11% by weight of Ti. The amounts of Be and Sr in each example are shown in Table 4.

[0141] [Table 4]

[0142] The test pieces of the examples shown in Table 4 were manufactured in the same manner as in Examples 1 to 15 of the first embodiment, and the casting test procedures were also the same as in the first embodiment. Note that the test pieces for which the Vickers hardness was measured were not subjected to heat treatment.

[0143] Table 4 shows the test results regarding the presence or absence of poor running in the 3.5 mm thick portion of the test piece.

[0144] Examples 42 to 44 do not contain Sr. As shown in Example 42, when the gate speed is as fast as 82 m / s, there is no molten metal running defect even without containing Be. As shown in Examples 43 and 44, when the gate speed is as slow as 59 m / s, Example 43, which does not contain Be, has molten metal running defect, but Example 44, which contains 0.0012 wt% Be, does not have molten metal running defect.

[0145] Examples 45 to 47 contain 0.005 wt% Sr. As shown in Example 45, when the gate speed is as fast as 82 m / s, there is no molten metal running defect even if Be is not contained. As shown in Examples 46 and 47, when the gate speed is as slow as 59 m / s, Example 46, which does not contain Be, has molten metal running defect, but Example 47, which contains 0.0011 wt% Be, does not have molten metal running defect.

[0146] Examples 48 and 49 contain 0.012% by weight of Sr. As shown in Examples 48 and 49, even when the gate speed is slow at 59 m / s, there is no poor running in Examples 48 and 49, which contain 0.0021% by weight and 0.0033% by weight of Be, respectively.

[0147] As described above, when Be is not added, poor molten metal running occurs when the gate speed is reduced by about 30%. On the other hand, by adding 0.0005 wt% or more of Be, poor molten metal running is improved regardless of whether Sr is added or not.

[0148] Furthermore, as shown in Examples 45 to 47 in Table 4, there is no difference in hardness depending on the Be content, and all of them show a Vickers hardness of 80 Hv or more.

[0149] [Fifth embodiment] A sand casting product according to a fifth embodiment of the present invention contains 4.0 to 11.0 weight % Si, 0.51 to 0.80 weight % Mg, 0.1 to 1.0 weight % Cu, 0.2 weight % or less Mn, 0.30 weight % or less Fe, 0.20 weight % or less Ti, 0.005 to 0.030 weight % Sr, 0.0050 weight % or less Be, and a total amount of unavoidable impurities of 0.50 weight % or less, with the balance being Al, and contains, as Fe compounds in the metallographic structure, one or more of an Al-Fe-Si compound and an Al-Fe-Si-Mn compound, and an Al-Fe-Si-Mg compound, and contains, as Cu compounds in the metallographic structure, an Al-Cu-Mg compound, and precipitates containing Cu atoms and Mg atoms, and has a Vickers hardness of 80 Hv or more and 110 Hv or less.

[0150] (Sand casting products) The sand cast product in this embodiment contains Si, Mg, Cu, Mn, Fe, Ti, Sr and inevitable impurities in weight percentages similar to those in the second and third embodiments, and may further contain Be.

[0151] In the sand casting product of this embodiment, Sr, which is added to improve elongation, reduces the fluidity of the molten metal due to its high oxide generating ability. Furthermore, a high content of Mg reduces the fluidity of the molten metal. Therefore, in order to suppress the oxidation of Sr and Mg and to improve the fluidity of the molten metal, 0.0050 wt% or less of Be is contained. To improve the fluidity of the molten metal, the amount of Be is preferably 0.0005 wt% to 0.0050 wt%.

[0152] (Metal structure of sand casting products) Basically, the sand cast product of this embodiment has the same metal structure as the second and third examples.

[0153] (Method of manufacturing sand casting products) Basically, it is manufactured in the same manner as in the second and third embodiments.

[0154] [Example] (Example of sand casting product) Table 5 shows the chemical composition and mechanical properties of the sand casting product according to this embodiment. The test pieces of the comparative examples and examples shown in Table 5 contain Al, 7.0 wt% Si, 0.57 wt% Mg, 0.30 wt% Cu, and 0.14 wt% Ti. The Be and Sr contents of each comparative example and example are shown in Table 5.

[0155] [Table 5]

[0156] In the mold flow length test, the results of which are shown in Table 5, a pouring tank was placed on the upper end of the mold, the stopper was removed, the molten metal was filled into the mold in an Ar atmosphere, and the length from the center of the spiral to the tip was measured. The size of the mold flow length test was 10 mm thick x 10 mm wide x flow length (mm), and the casting temperature was 650°C. For the test pieces used to measure Vickers hardness, T6 treatment was applied to 10 mm square sand casting material. Specifically, the treatment was 530°C x 2 hours ⇒ water quenching ⇒ left at room temperature for 2 hours ⇒ 160°C x 5 hours.

[0157] Table 5 shows the test results for the flow length and hardness of the test pieces.

[0158] Comparative Examples 21 to 23 do not contain Sr. Comparative Examples 21 to 23 contain 0.0000 to 0.0011 weight % of Be. As shown in Comparative Examples 21 to 23, by increasing the content of Be, the flow length is lengthened and the fluidity of the molten metal is improved.

[0159] Examples 50 to 54 contain 0.012 wt % Sr. Examples 50 to 54 contain 0.0000 to 0.0032 wt % Be. As shown in Examples 50 to 54, the more Be is added, the longer the flow length becomes, and the more the molten metal flow improves.

[0160] As shown in Table 5, the flow length is increased and the fluidity is improved by adding 0.0005 wt% or more of Be, regardless of whether Sr is added or not. Examples 50 to 54, which contain Sr, require a higher amount of Be to achieve the same flow length, compared to Comparative Examples 21 to 23, which do not contain Sr.

[0161] Furthermore, as shown in Examples 50 to 54 in Table 5, there is no difference in hardness depending on the Be content, and all of them show a Vickers hardness of 80 Hv or more.

Claims

1. Molten aluminum alloy is poured into the mold product portion, The molten aluminum alloy is solidified in the mold product portion. The time from pouring the molten metal to removing the casting from the mold product portion is set to within one minute, and age hardening is performed within the time.

1. A method for producing a die cast product, comprising the steps of: The die-cast product is containing 6.0 to 11.0 mass% Si, 0.51 to 1.00 mass% Mg, 0.1 to 1.0 mass% Cu, 0.1 to 0.7 mass% Mn, 0.50 mass% or less Fe, 0.20 mass% or less Ti, 0.03 mass% or less Sr, and unavoidable impurities in a total amount of 0.50 mass% or less, with the balance being Al; The metal structure contains, as Fe compounds, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds, The metal structure contains, as Cu compounds, Al-Cu-Mg compounds and precipitates containing Cu atoms and Mg atoms, Vickers hardness is 80Hv or more and 110Hv or less. A manufacturing method for die-cast products.

2. The die-cast product is Contains at least one of 6.0 to 8.9 mass% Si, 0.51 to 0.80 mass% Mg, 0.1 to 0.6 mass% Cu, 0.31 to 0.50 mass% Mn, 0.40 mass% or less Fe, and 0.003 to 0.030 mass% Sr. A method for producing the die-cast product according to claim 1.

3. The die-cast product is The alloy has primary α-Al grains and a mesh-like eutectic portion surrounding the primary α-Al grains, and the eutectic portion has fine granular Al having a grain size smaller than that of the primary α-Al grains. A method for producing a die-cast product according to claim 1 or 2.

4. containing 6.0 to 11.0 mass% Si, 0.51 to 1.00 mass% Mg, 0.1 to 1.0 mass% Cu, 0.1 to 0.7 mass% Mn, 0.50 mass% or less Fe, 0.20 mass% or less Ti, 0.03 mass% or less Sr, 0.0050 mass% or less Be, and unavoidable impurities in a total amount of 0.50 mass% or less, with the balance being Al; The metal structure contains, as Fe compounds, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds, The metal structure contains, as Cu compounds, Al-Cu-Mg compounds and precipitates containing Cu atoms and Mg atoms, Vickers hardness is 80Hv or more and 110Hv or less. Die-cast product.

5. Contains at least one of 6.0 to 8.9 mass% Si, 0.51 to 0.80 mass% Mg, 0.1 to 0.6 mass% Cu, 0.31 to 0.50 mass% Mn, 0.40 mass% or less Fe, and 0.003 to 0.030 mass% Sr. The die-cast product according to claim 4.

6. Molten aluminum alloy is poured into the mold product area, The molten aluminum alloy is solidified in the mold product portion. The time from pouring the molten metal to removing the casting from the mold product portion is set to within one minute, and age hardening is allowed to proceed within the time period. A method for manufacturing the die-cast product according to claim 4 or 5. A manufacturing method for die-cast products.

7. A steel sheet comprising 6.0 to 11.0 mass% Si, 0.51 to 1.00 mass% Mg, 0.1 to 1.0 mass% Cu, 0.1 to 0.7 mass% Mn, 0.50 mass% or less Fe, 0.20 mass% or less Ti, 0.03 mass% or less Sr, and unavoidable impurities in a total amount of 0.50 mass% or less, with the remainder being Al; The metal structure contains, as Fe compounds, Al-Fe-Si compounds, Al-Fe-Si-Mn compounds, and Al-Fe-Si-Mg compounds, The metal structure contains, as Cu compounds, Al-Cu-Mg compounds and precipitates containing Cu atoms and Mg atoms, The metal structure has primary crystal α-Al grains and a network-like eutectic portion surrounding the primary crystal α-Al grains, The eutectic portion contains fine Al particles having a diameter of 10 μm or less, Vickers hardness is 80Hv or more and 110Hv or less. Die-cast product.

Citation Information

Patent Citations

  • Manufacture of aluminum alloy for casting and aluminum alloy casting

    JP1989283336A

  • Die-cast aluminum alloys for structural components

    JP2023510881A

  • Die-casting aluminum alloy without heat-treatment and preparation method and automobile structural part

    JP2024066509A

  • Aluminum alloy and die casting method

    WO2015151369A1

  • Aluminum alloy for die casting and functional components using same

    WO2019059147A1